Sustainable road infrastructure project implementation in developing countries : an integrated model - Ametepey, Simon Ofori; Aigbavboa, Clinton Ohis; Thwala, Wellington Didibhuku (Emerald Publishing Limited, 2023)
Seven of the seventeen United Nations Sustainable Development Goals (UNSDGs) are directly related to sustainable infrastructure development. The majority of sectors, including the road infrastructure sector, are under intense pressure to find financially feasible, socially acceptable, and environmentally conscientious project outcomes or techniques that will result in sustainable road infrastructure development (SRID). Sustainable Road Infrastructure Project Implementation in Developing Countries presents a model for implementing sustainable road infrastructure projects in developing countries. Providing readers with comprehensive theoretical and practical directions on implementing sustainable road infrastructure projects in developing countries successfully, the authors discuss the factors which influence the implementation of sustainable road infrastructure projects, including the drivers, barriers, benefits, and determinants of sustainable road project implementation. The model offers road infrastructure stakeholders with a precise and functional tool that promotes collaboration, common language and comprehension, engagement and interaction among all individuals and institutions involved in SRIP implementation. It is beneficial to both professionals and scholars, in the area of architecture; building technology; civil engineering; sustainable/green construction and other disciplines in the built industry.